Factors affecting the dividend policy: an econometric study of Saidal Corporation listed on the Algiers Stock Exchange for the Period 2002-2021 - hamrit, abdenacer; slimani, Mohamed (Journal of Research in Finance and Accounting, 2023)
This study aims at highlighting the main factors affecting dividend policy. The study used a sample of 80 quarterly observation for Saidal corporation, listed in the Algerian Stock Exchange during the period 2002-2021. Using Robust regression technique to estimate the multiple linear regression model that describe the relationship. The study concluded that profitability, liquidity, financial leverage, size, growth rate have an inverse significant effect on the dividend decision, while risk has an inverse but significant weak effect for the corporation concerned.